Strategies to improve the performance of learners in a nursing college Part II: Issues pertaining to management, attitudes and values - E Waterson; E Harms; L Qupe; J Maritz; M Manning; K Makobe; M Chabeli (AOSIS, 2006)
This article forms part two of a bigger study that was conducted in a nursing college to explore and describe the reasons for the poor performance of learners. Part one of the study dealt with the issues pertaining to education, while this article (part two) seeks to describe issues pertaining to management, attitudes and values that lead to the poor performance of learners in the nursing college under study. A qualitative, exploratory and descriptive design that was contextual in nature was employed, and three focus groups interviews were conducted. Seven tutors formed one group while other two groups were formed by fourth-year learners following a comprehensive diploma course. All participants voluntarily participated in the study. Data was analyzed using the descriptive method of open coding in accordance with Tesch's protocol (in Creswell, 1994:154-156). Trustworthiness was ensured using the following principles: credibility, conformability, transferability and dependability (Lincoln & Guba 1985:290-326). Findings were categorized into issues pertaining to management, attitudes and values that had an influence on the poor performance of learners as follows: Management: Inadequate resources and study facilities; policies that change frequently; tutors' dissatisfaction with regard to staff development, the lack of involvement by management and lack of management support, staff shortage and maldistribution of staff members; ineffective selection process of learners; inconsistent regulations, and too many of them; policies and procedures resulting in confusion and poor discipline. Attitudes and values: Tutors' lack of motivation and interest, lack of respect by learners and no team work among tutors.Through a conceptualization process and the recommendations by participants, strategies to improve the learners' performance were described. It is recommended that these strategies be submitted to the staff development committee for implementation and future follow-up research be undertaken to determine the effectiveness of the strategies. It is also recommended that other nursing colleges replicate the study within their context.